2017
DOI: 10.1111/hae.13274
|View full text |Cite
|
Sign up to set email alerts
|

Deficits of ankle muscle strength not found in children, adolescents and young adults with haemophilic ankle arthropathy

Abstract: Contrarily to adult patients, CAAwH with repeated ankle bleeding may be less impaired than current structural evaluations imply, with possibly a latency between the occurrence of structural and functional damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…We previously reported on isokinetic muscle strength in the same CAAwH group, finding it unaltered in TTJ and STJ arthropathy. There were no differences observed between affected and non‐affected sides in CAAwH with unilateral arthropathy.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We previously reported on isokinetic muscle strength in the same CAAwH group, finding it unaltered in TTJ and STJ arthropathy. There were no differences observed between affected and non‐affected sides in CAAwH with unilateral arthropathy.…”
Section: Discussionmentioning
confidence: 69%
“…Stephensen et al 22 identified ankle plantarflexor muscle atrophy in children with haemophilia using ultrasound images. In their study, nineteen boys with severe haemophilia aged 6-12 years and a history of minimum of three bleeds into the same ankle since birth showed smaller lateral We previously reported on isokinetic muscle strength in the same CAAwH group, 23 finding it unaltered in TTJ and STJ arthropathy. There were no differences observed between affected and non-affected sides in CAAwH with unilateral arthropathy.…”
Section: Discussionmentioning
confidence: 78%
“…As such, Stephensen et al 7 demonstrated that children with haemophilia (CwH) with a history of structural ankle damage had a significant reduction in strength of the knee extensors, ankle dorsiflexors and ankle plantar flexors. These findings were not confirmed in a more recent study by Lobet et al (2017) who found that children and adolescents with haemophilic arthropathy are functionally less disabled than structural evaluations would suggest, contrarily to adult patients, 8 who present progressive quadriceps weakness with increasing age stages, as compared to healthy individuals 9 . More recently, Lobet et al 10 studied the effect of structural joint damage on the elastic stiffness of the ankle in CwH and highlighted that the latter was significantly increased in children and adults with unilateral affected ankle joints compared to the non‐affected side.…”
Section: Introductionmentioning
confidence: 66%
“…Data were gathered on 163 patients with haemophilia over the age of 16 who had presented to the Coagulopathies Department of our Hospital for a routine musculoskeletal assessment between 2012 and 2017. Children were excluded given their high prevalence of congenital pes planovalgus and because they tend to be less prone to functional impairment . An evaluation was conducted of the patients’ social and demographic characteristics, including age, type of haemophilia, severity of disease, presence of inhibitors and haematologic treatment regimen (prophylactic or on demand).…”
Section: Methodsmentioning
confidence: 99%